2011
DOI: 10.1142/s0192415x1100883x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic PTP1B Expression Involvement in the Effects of Chinese Medicine Formula Xiao-Gao-Jiang-Zhuo Using an Obese Rat Model

Abstract: In this study, we investigated the effects of a Chinese herbal medicine formula xiao-gao-jiang-zhuo (XGJZ) in obese rats induced by a high-fat diet. Ten male rats in the normal group were fed with a standard diet. Another 50 male obese rats were induced by a 12-week high-fat diet feeding, and were randomly divided into five groups (n = 10 per group): the model group, the high-dose XGJZ group, the middle-dose XGJZ group, the low-dose XGJZ group, and the sibutramine group. After 14 weeks of treatment, body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…current efficiency was only 22 % in used FFC to electrolyze the Cr 2 O 3 for 6 h. Wang and Zhai 55 found that the current efficiency was only 22.7 % in the molten salt electrolysis prepared CaB 6 . Li et al 56 reported that O 2diffusion and the anode materials could be the main factors affecting the electrolysis efficiency and they could limit the exclusion of the same kind of ions and the attraction of the opposite ions in O 2diffusion process. Li et al 57 analyzed the C contamination of the molten-salt electrolysis preparation of Ti and they considered that the electrolysis conditions and CO 2 production could affect C content of products.…”
mentioning
confidence: 99%
“…current efficiency was only 22 % in used FFC to electrolyze the Cr 2 O 3 for 6 h. Wang and Zhai 55 found that the current efficiency was only 22.7 % in the molten salt electrolysis prepared CaB 6 . Li et al 56 reported that O 2diffusion and the anode materials could be the main factors affecting the electrolysis efficiency and they could limit the exclusion of the same kind of ions and the attraction of the opposite ions in O 2diffusion process. Li et al 57 analyzed the C contamination of the molten-salt electrolysis preparation of Ti and they considered that the electrolysis conditions and CO 2 production could affect C content of products.…”
mentioning
confidence: 99%